Teacher preparation in Portugal: navigating the tides of change - Moreira, Maria Alfredo (2018)
This paper will address teacher preparation programs in Portugal for K-12 schools, providing an empirical and theoretical analysis of educational policies after the implementation of the Bologna Process in Higher Education in Europe. Before Bologna, there was a boom in the private offer of these programs, fueled by the millions of euros from the European Union’s structural funds. Under right-wing governments and with the argument of the low educational quality indicators, there was a complete deregulation of the teacher education “market”. With the Bologna Process, teacher preparation was condensed into one and a half to two years, following a 1st cycle of studies of 3-4 years. The systematic financial asphyxiation of the public institutions led to severe downsizing of higher education programs and teaching staff, in the legitimization of revised funding policies (cf. Paraskeva, 2012, p. 63), created tensions due to the resulting battles for survival on the job, while opening the door for the corporatization of higher education (Giroux, 2015). In addition, the economic and financial austerity that resulted from the country’s bailout from the IMF, the Central European Bank and the European Commission, associated with high unemployment among teachers and declining demographics, caused a strong retraction in the hiring of teachers by the main employer - the State. Public institutions were severely affected, but private ones took the greatest toll. With the demand of a Master in Teaching qualification, the private institutions, the majority of which were not investing in the qualification of their staff, could not cope with the demands of quality imposed by the Agency for Assessment and Accreditation of Higher Education (AAAHE). Thus, contrary to policy movements in the USA, Brazil or Chile (see Zeichner, 2013), teacher preparation in Portugal currently does not favor the private sector. In spite of being bankrupt (Paraskeva, 2012), a public good continuously under menace (Santos, 2004) for the continuing disinvestment on people and on the system itself (Silva, 2009), teacher preparation in public higher education in Portugal is surviving and regaining a place once hotly disputed with the private sector. The conclusions sketched in this proposal will be substantiated by statistical data, theoretical and document analysis, from varied sources like official organisms (the AAAHE) and relevant literature review.